In vivo evidence for a regulatory role of phosphorylation of Arabidopsis Rubisco activase at the Thr78 site - Kim, Sang Yeol (Proc Natl Acad Sci U S A, 2019)
Arabidopsis Rubisco activase (Rca) is phosphorylated at threonine-78 (Thr78) in low light and in the dark, suggesting a potential regulatory role in photosynthesis, but this has not been directly tested. To do so, we transformed an rca-knockdown mutant largely lacking redox regulation with wild-type Rca-β or Rca-β with Thr78-to-Ala (T78A) or Thr78-to-Ser (T78S) site–directed mutations. Interestingly, the T78S mutant was hyperphosphorylated at the Ser78 site relative to Thr78 of the Rca-β wild-type control, as evidenced by immunoblotting with custom antibodies and quantitative mass spectrometry. Moreover, plants expressing the T78S mutation had reduced photosynthesis and quantum efficiency of photosystem II (ϕ(PSII)) and reduced growth relative to control plants expressing wild-type Rca-β under all conditions tested. Gene expression was also altered in a manner consistent with reduced growth. In contrast, plants expressing Rca-β with the phospho-null T78A mutation had faster photosynthetic induction kinetics and increased ϕ(PSII) relative to Rca-β controls. While expression of the wild-type Rca-β or the T78A mutant fully rescued the slow-growth phenotype of the rca-knockdown mutant grown in a square-wave light regime, the T78A mutants grew faster than the Rca-β control plants at low light (30 µmol photons m(−2) s(−1)) and in a fluctuating low-light/high-light environment. Collectively, these results suggest that phosphorylation of Thr78 (or Ser78 in the T78S mutant) plays a negative regulatory role in vivo and provides an explanation for the absence of Ser at position 78 in terrestrial plant species.